ACADEMIC SELF CONCEPT AND ENGLISH LANGUAGE LEARNING ACHIEVEMENT - Permatasari, Septika Indah; Susilawati, Endang; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research concentrated on academic self-concept (ASC) of the students at Hidayatul Muslimin 1, Islamic Junior High Boarding School Kubu Raya who have high and low academic achievement (ACA) in English class. The sample consisted of 27 girl students. It was classified into 10 students who marked as high achievers and 17 others who marked as low achievers from eight class. The method of this research was descriptive and correlation. ASC was measured through Academic Self Concept Scale while ACA was measured from studentsâ€™ English Mid Term Test scores. The mean score of ASC from high achievers is 64.20 classified as positive academic self-concept while from low achievers is 12.44 classified as negative academic self-concept. The correlation of ASC and ACA of high achievers is 0.06 which means very weak because there were some students who got high ACA but have negative ASC while low achievers is 0.41 which means moderate because there were some students who got low ACA but had neutral ASC. Therefore, the research findings show that the English ACA were not always followed by the positive ASC but might be affected by other factors.Â Keywords:Effective, Learning Outcomes, Learning Models Examples Non Examples, Historical Subjects.